A Good Year - Malaysian Universities Improved Considerably In The (THE)-QS World University Rankings 2008 After Last Year's Steep Slide - Sunday Star, Karen Chapman (2008)
THERE was good news for Malaysian public universities this year in the Times Higher Education (THE)-QS World University Rankings 2008.